2018
DOI: 10.3389/fpls.2018.00156
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of HKT1;5 Gene in Barley Using GWAS Approach and Its Implication in Salt Tolerance Mechanism

Abstract: Sodium (Na+) accumulation in the cytosol will result in ion homeostasis imbalance and toxicity of transpiring leaves. Studies of salinity tolerance in the diploid wheat ancestor Triticum monococcum showed that HKT1;5-like gene was a major gene in the QTL for salt tolerance, named Nax2. In the present study, we were interested in investigating the molecular mechanisms underpinning the role of the HKT1;5 gene in salt tolerance in barley (Hordeum vulgare). A USDA mini-core collection of 2,671 barley lines, part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 77 publications
5
47
0
Order By: Relevance
“…n 43, n 23 and n 27) accumulated much lower Na in the leaves and roots, as compared to those of salinity‐sensitive genotypes (cultivars and a few wild barley genotypes). These findings were consistent with the previous studies on the wild grasses in which the critical role of the sodium (Na) ion in salinity tolerance has been highlighted, particularly at high levels of salinity stress (Arabbeigi et al, ; Hazzouri et al, ; Kiani, Arzani, & Habibi, ; Rezaei et al, ). The effects of the salinity stress on the leaf and root ionic contents also showed that the K concentration and K/Na ratio were significantly decreased under salinity conditions (Table ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…n 43, n 23 and n 27) accumulated much lower Na in the leaves and roots, as compared to those of salinity‐sensitive genotypes (cultivars and a few wild barley genotypes). These findings were consistent with the previous studies on the wild grasses in which the critical role of the sodium (Na) ion in salinity tolerance has been highlighted, particularly at high levels of salinity stress (Arabbeigi et al, ; Hazzouri et al, ; Kiani, Arzani, & Habibi, ; Rezaei et al, ). The effects of the salinity stress on the leaf and root ionic contents also showed that the K concentration and K/Na ratio were significantly decreased under salinity conditions (Table ).…”
Section: Discussionsupporting
confidence: 92%
“…The ability to discriminate between Na and K in the soil solution and to preferentially exclude Na and accumulate K in the plant tissues has been recognized as the important contributors to salinity tolerance in the tribe Triticeae (Dvorak, Noaman, Goyai, & Gorham, ; Hazzouri et al, ; Shabala, Hariadia, & Jacobsen, ; Zhu, Shabala, Shabala, Fan, & Zhou, ). Hazzouri et al () demonstrated that HKT1;5 gene plays a key role in withdrawing Na from the xylem and therefore reducing its transport to the leaves in barley.…”
Section: Discussionmentioning
confidence: 99%
“…However, the root expression was higher in roots of tolerant plants compared to sensitive which may explain its involvement in tolerance. As HKT1-driven tolerance is linked to the tissue-specific expression in other species [90][91][92], leaf and shoot expression would be necessary for explaining the phenotype of the studied populations. Regarding to the Clexclusion, both in DV and BC t tolerant populations, lower content in Clcan be associated with the lower relative values of g s and E compared to the control populations.…”
Section: Ionic Stress Responsesmentioning
confidence: 99%
“…The significantly associated region spanned approximately 6.6Mb, from 638,211,825 nt to 644,818,273 nt on the barley 4H physical map 21 and contained 247 gene models ( Supplementary Table 2 ). Common SNPs between the 50k and 9K iSelect platforms 22 aligned this association with a region recently shown to contain HvHKT1;5 20, 23 , and in the barley genome sequence HORVU4Hr1G087960, 140kb from the top scoring SNP (chr4H_638774955), was annotated as a homolog of OsHKT1;5. Considering this and previous functional studies 2427 we conclude that HORVU4Hr1G087960 is the Na + specific transporter HvHKT1;5 .…”
Section: Resultsmentioning
confidence: 73%